2006
DOI: 10.1111/j.1467-9450.2006.00519.x
|View full text |Cite
|
Sign up to set email alerts
|

Work‐related stress and well‐being: The roles of direct action coping and palliative coping

Abstract: . Work-related stress and well-being: The roles of direct action coping and palliative coping. Scandinavian Journal of Psychology , 47 ,[293][294][295][296][297][298][299][300][301][302] The purpose of the present study is to analyze the roles of direct action coping and palliative coping in the relationship between work stressors and psychological well-being, as well as their possible interactions, in a sample of 464 bank employees. Hierarchical regression analyses showed main effects of direct action coping … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
40
1
6

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 45 publications
7
40
1
6
Order By: Relevance
“…In both cases the level of action-focused coping hardly affects the variation. Combining action and emotion coping strategies has significant effects as pointed out by Fortes-Ferreira et al (2006), and by Shimazu and Kosugi (2003), but it should be noted that excessive use of emotion-focused coping might end up cancelling the beneficial effects of action-focused coping. That is, although action-focused coping strategies, pointed directly on the problem or stressor, have good results to combat the sources of stress, however the prolonged use of these strategies can cause great deterioration on the subject so that the combined use of action and emotion anales de psicología, 2017, vol.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In both cases the level of action-focused coping hardly affects the variation. Combining action and emotion coping strategies has significant effects as pointed out by Fortes-Ferreira et al (2006), and by Shimazu and Kosugi (2003), but it should be noted that excessive use of emotion-focused coping might end up cancelling the beneficial effects of action-focused coping. That is, although action-focused coping strategies, pointed directly on the problem or stressor, have good results to combat the sources of stress, however the prolonged use of these strategies can cause great deterioration on the subject so that the combined use of action and emotion anales de psicología, 2017, vol.…”
Section: Discussionmentioning
confidence: 99%
“…The selection of items was made on the basis of expert judgment, keeping in mind the Steiler and Paty, (2009) factorial solution of two factors and the concept validity of action-focused coping and palliative coping (Lazarus & Folkman, 1984;Dewe, 1989). This procedure has been used in a similar way in previous research (Fortes-Ferreira et al 2006). A confirmatory factor analysis confirms an adequate overall fit of the two-factors model (goodness of fit index = .93; adjusted goodness of fit index = .91; root mean square error of approximation = .07).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…active) coping strategies. Recent empirical research among bank employees revealed that active coping (''direct action coping'') positively predicted job satisfaction and negatively predicted psychological distress (Fortes-Ferreira, Peiró, Conzález-Morales, & Martin, 2006). The relationship between control and pro-active behaviour is also reflected in taxonomies concerning conflict management strategies that are based on the Dual Concern Model (Blake & Mouton, 1964;Rubin, Pruitt, & Kim, 1992).…”
Section: Locus Of Controlmentioning
confidence: 99%
“…Yulong and his colleagues also reported that increased coping resources (e.g., selfcare, social support, recreation and rational coping) had a buffering effect on the relationship between work-related psychosocial factors and psychological distress (Lian et al, 2016). On the contrary, other studies have only provided weak (Bhagat et al, 1995;Greenglass et al, 1990) or no (Fortes-Ferreira et al, 2006;Rick and Guppy, 1994) interaction effect between coping resources and psychological distress in the work environment.Uncertainty as to the role of coping resources with regards to the modulation of psychological distress in the workplace probably reflects methodological issues associated with clarifying any relationship. The interaction effect between the different coping resources (coping strategies, and social support) and their capacity to impact psychological distress has been insufficiently studied.…”
mentioning
confidence: 88%